RESPON PERTUMBUHAN DAN HASIL PADI (Oriza sativa L.) VARIETAS INPARI 42, CIHERANG DAN MEKONGGA TERHADAP BERBAGAI METODE TANAM JAJAR LEGOWO - Ahyani Tajudin; Iman Sungkawa (Agroswagati Jurnal Agronomi, 2021)
This study aims to determine: (1) The response to growth and yield of rice in Inpari 42, Ciherang and Mekongga varieties to various planting methods of Jajar Legowo, and (2) Varieties and planting methods of legowo row which have a good effect on rice growth and yield. The research was carried out in a rice field area belonging to the UPTD of the Food and Agriculture Security Service in Cirahayu Village, Luragung District, Kuningan Regency, from April to June 2020. The method used in this study was an experimental method, using a randomized block design (RBD), which consisted of 15 treatments of combination of rice varieties and the legowo row planting method and was repeated three times. To determine the effect of the treatments tested, analysis of variance was used through the F test, with further tests using Scott Knott's Cluster Test at the 5 percent real level. The results showed that: (1) The treatment of three rice varieties on various planting methods had significant effects on the growth and yield of rice plants. The 2 : 1 legowo row planting method on three rice varieties affected the plant height of harvested dry grain and milled dry grain per plot, while the 4 : 1 legowo row planting method in three rice varieties had an effect on the number of tillers per hill, the number of productive tillers per hill, leaf area index, number of panicles per clump, number of grains per panicle, number of filled grains per panicle, weight of 1000 grains of grain. The Ciherang variety has a good effect on the weight of 1000 grain grains, while the Inpari 42 variety has a good effect on the yield of dry grain harvested and the yield of milled dry grain per plot, and (2) the combination of Inpari 42 variety with the 2: 1 legowo row planting method gives good effect on yields of harvested dry unhulled rice and yields of milled dry unhulled rice per plot, which is 9.27 kg or equivalent to 10.30 tons of dry unhulled rice per hectare, and 7.81 kg of dry unhulled rice per plot or equivalent to 8.68 tons of unhulled rice dry milled oer acres.